1978
DOI: 10.1042/cs0550213
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Cholecalciferol Absorption in the Elderly and in Younger Adults

Abstract: 1. A method for assessing cholecalciferol absorption in man is described. 2. The intestinal absorption of [3H]cholecalciferol was studied in 20 female geriatric patients, most of whom were vitamin D-depleted. 3. The plasma [3H]cholecalciferol response after oral ingestion was significantly lower than that of a group of younger female subjects. 4. The plasma response of labelled polar metabolites of cholecalciferol was also lower in the geriatric than in the younger group, suggesting that increased removal of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 17 publications
2
60
0
Order By: Relevance
“…The estimated half-life of 25OHD in infants is 2-3 wk (717), similar to values in adults (59,62,189,344,449), which means that a higher cord blood 25OHD will only influence neonatal levels over about the first 6 wk. Randomized intervention studies indicate that typical maternal vitamin D doses of 400-1,000 IU/day do not consistently increase breast milk content of vitamin D or 25OHD, whereas with maternal vitamin D doses of 2,000 -4,000 IU/day, an increase in milk content of vitamin D and 25OHD and neonatal 25OHD can be demonstrated (13,14,402,780).…”
Section: Human Datamentioning
confidence: 58%
“…The estimated half-life of 25OHD in infants is 2-3 wk (717), similar to values in adults (59,62,189,344,449), which means that a higher cord blood 25OHD will only influence neonatal levels over about the first 6 wk. Randomized intervention studies indicate that typical maternal vitamin D doses of 400-1,000 IU/day do not consistently increase breast milk content of vitamin D or 25OHD, whereas with maternal vitamin D doses of 2,000 -4,000 IU/day, an increase in milk content of vitamin D and 25OHD and neonatal 25OHD can be demonstrated (13,14,402,780).…”
Section: Human Datamentioning
confidence: 58%
“…of total 25-hydroxyvitamin D (25-OH D) (5 ) because the half-life of 25-OH D is ϳ3 weeks whereas the half-life of vitD is ϳ24 h (6,7 ). Dietary supplementation of food and vitamin tablets comes in the form of both vitD 2 and vitD 3 ; it is therefore essential that both analytes are measured equimolarly.…”
mentioning
confidence: 99%
“…But a cross-sectional study conducted by Alhumaidia et al 21 found a contrasting result. Vitamin D status is known to be lower in the elderly compared with the young as the subcutaneous synthesis of vitamin D decreases with increasing age, due to a reduced concentration of 7-dehydrocholesterol in the skin 22 and reduced absorption of oral vitamin D. 23 Even though our study found a inverse association between duration and mean Vitamin D levels, the age difference between study groups must be taken into account.…”
Section: Resultsmentioning
confidence: 52%